Can school nurses improve the school environment in Norwegian primary schools? A protocol for a randomized controlled trial. (2019) - Federici, Roger Andre; Flatø, Martin; Bru, Lars Edvin; Midthassel, Unni Vere; Helleve, Arnfinn; Rønsen, Ester
Highlights: This protocol describes a randomised controlled trial where additional school nurse resources are assigned to work systemically with schools. The additional school nurse resource should work to improve the school environment and reduce bullying and absence for 5th to 7th grade students. Approximately 9000 students participate each year from 2018 to 2020 in 107 schools located in 12 Norwegian municipalities. Academic performance is studied as a secondary outcome. Abstract: This protocol describes a randomized controlled trial where additional school nurse resources are assigned to work systemically with schools to improve the school environment and reduce bullying among and absence of 5th–7th grade students. Approximately 9000 students will have participated each year from 2018 to 2020 from 107 schools located in 12 Norwegian municipalities. Academic performance is studied as a secondary outcome.